The signature of galaxy formation models in the power spectrum of the hydrogen 21 cm line during reionization - Lewis, Joseph; Pillepich, Annalisa; Nelson, Dylan; Klessen, Ralf S.; Glover, Simon (Monthly notices of the Royal Astronomical Society, 2024)
Observations of the 21 cm line of hydrogen are poised to revolutionize our knowledge of reionization and the first galaxies. However, harnessing such information requires robust and comprehensive theoretical modelling. We study the non-linear effects of hydrodynamics and astrophysical feedback processes, including stellar and AGN feedback, on the 21 cm signal by post-processing three existing cosmological hydrodynamical simulations of galaxy formation: Illustris, IllustrisTNG, and Eagle. Despite their different underlying galaxy-formation models, the simulations return similar predictions for the global 21 cm brightness temperature and its power spectrum. At fixed redshift, most differences are attributable to alternative reionization histories, in turn driven by differences in the buildup of stellar sources of radiation. However, several astrophysical processes imprint signatures in the 21 cm power spectrum at two key scales. First, we find significant small-scale